The impact of Kamala Harris’s social identities during the 2024 presidential election - Emily J. Brown; Sheba M. Aikawa; Evava S. Pietri; Tiffany A. Ito (PLoS ONE, 2026)
The social identities of Democratic Party presidential nominee Kamala Harris were noted frequently prior to the 2024 United States Election. We examined how making salient her marginalized racial and gender identities affected evaluations of her prior to the election. In Study 1, a stratified U.S. sample viewed a paragraph describing only Harris’s qualifications or her qualifications along with her gender, race, or both. Mentioning her race led to less favorable perceptions regardless of participants’ political orientation, suggesting subtle identity cues shape impressions. Political orientation did moderate responses when Harris was compared to an unnamed candidate, with more conservative participants rating Harris less favorably. Study 2 disaggregated Harris’s racial background showing that her Black identity, not her South Asian or combined racial identity, drove the negative evaluations across participant political orientation. As in Study 1, conservatives rated her more negatively than an unnamed candidate, but only when her Black identity was made salient. Together, these studies demonstrate that identity salience, particularly Black racial identity, can meaningfully influence candidate evaluations.